(untitled) (Victoria Journal of Management, 2025)
This systematic literature review investigates the evolving role of financial literacy (DFL) in shaping financial behavior, inclusion, entrepreneurship, and engagement with digital technologies. Based on 52 peer reviewed articles published between 2010 and July 2025 from the Scopus database, the review highlights the growing significance of DFL in helping individuals effectively use digital financial services such as mobile banking, online payments, and investment platforms. The study is grounded in theoretical frameworks like the Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology, and Financial Literacy Theory, all emphasizing the role of literacy in technology adoption and financial empowerment. A noticeable increase in DFL research after 2022 reflects rising academic interest, with 98 percent of studies employing quantitative methods like regression and structural equation modeling. Research contributions are notably high from countries like Indonesia and India. The findings are grouped into five key themes: Financial Well-Being and Behavior accounting for 32.08 percent, Financial Inclusion and Access making up 24.53 percent, Entrepreneurship and Medium Small and Micro Enterprises (MSME) Development representing 18.87 percent, Digital Financial Technologies and Tools contributing 15.09 percent, and Women Empowerment and Gender Finance accounting for 9.43 percent. Evidence from countries such as South Korea, Indonesia, China, and India shows that DFL enhances savings habits, reduces financial stress, and improves financial confidence and inclusion, particularly among marginalized and underserved populations. The review concludes that DFL is crucial for building inclusive and sustainable financial systems. Despite its limitations, mainly relying on English-language, Scopus-indexed articles, the study provides valuable insights for policymakers, educators, and financial service providers. Future research should focus on exploring the long-term impacts of DFL and its dynamic interplay with emerging Fin Tech innovations.